Identification of peptide inhibitors of matrix metalloproteinase 1 using an in-house assay system for the enzyme - Min, Moon Won; Kim, Chae Eun; Chauhan, Sushma; Park, Hyeon Ji; Park, Chang Seo; Yoo, Tae Hyeon; Kang, Taek Jin (Enzyme and Microbial Technology, 2019)
Matrix metalloproteinases (MMPs) are zinc-dependent proteases involved in the degradation of extracellular matrix proteins. As one of the isoforms, MMP-1 breaks down collagen, and its activity is known to be important in wound healing. Its timely and adequate level of expression is pivotal because MMP-1 is also involved in the damage or aging of skins as well as in certain types of cancers. Thus, both assaying the MMP-1 activity and developing its inhibitors are of great importance. We here developed an in-house assay system that gave us the high degree of freedom in screening peptide inhibitors of MMP-1. The assay system utilized a circularly permutated fusion of β-lactamase and its inhibitory protein through an MMP-1-sensitive linker so that the activity of MMP-1 could be translated into that of β-lactamase. As a proof of concept, we applied the developed assay system to initial screens of MMP-1 inhibitors and successfully identified one lead peptide that inhibited the collagenase activity of the enzyme.
Keywords: Collagen degradations; Matrix metalloproteinase-1; Peptide inhibitors; Protease inhibition; Zymogen; Drug Evaluation, Preclinical; Matrix Metalloproteinase 1; Matrix Metalloproteinase Inhibitors; Peptides; Collagen degradation; Matrix metalloproteinase 1; Peptide inhibitor; Protease inhibition; Zymogen